Military Expense in the State of Bolivar. 1859-1886 - Pardo Bueno, Luis Miguel (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article studies the evolution of military expense in the State of Bolívar between the years of 1859 and 1889, during the governments of radical liberalism in the United States of Colombia. The data for this research was compiled from the Gaceta de Bolívar and other oficial documents, such as the public annual budgets of the State. The interest of this research was the expense analysis of the administrative department of the milicia. The main objective was to demostrate how the politics of radical liberalism focused on iscal and military descentralization, with the aim of strengthening local powers, handing over the control and administration of the inancial resources of the State of Bolívar and its milicia to the regional elite. For this purpose, this research analyzes the forms of inancing in the State militia and the internal costs of its functioning, accounting for the scarce budget allocation for paying wages, war material, military education and health service. This led to a practice by which the State militia demanded private funding from society in order to cover expropriations and loans, the necessary budget lines for its organization and operation.